Preschool childrens level of semantic acquisition through childrens songs, stories and animated films on YouTube - Kamarudin, Kamariah; Zainon Hamzah, Zaitul Azma; Maming, Pabiyah Haji; Bahar, Ida Baizura; Abdul Rahman, Haliza; Mansor, Nor Shahila (Human Resource Management Academic Research Society, 2023)
Semantic acquisition is the process of a child acquiring eclectic meanings of linguistic elements and conceptual senses. This gradual process starts before a child says their first word, which includes many different types of words. The use of digital technology approaches to examine children’s linguistic environment can benefit children’s language development and make more detailed predictions about what, when, where and how semantic development assists children’s language development. Hence, this study attempts to identify the level of semantic acquisition of preschool children using children’s songs and stories as well as animated films in YouTube and summarise the types of words children acquire from them. This study employed the observation method and its study sample comprised 50 preschool children selected using a purposive sampling technique. The research data consisted of two children’s stories, three children’s songs and two animated films downloaded from YouTube. The findings show that the acquisition of synonyms happens at a basic level, 94. Similarly, the acquisition of antonyms occurs at a basic level, 38, while the acquisition of hyponyms occurs at a low level, 44. Therefore, it established that the level of acquisition for hyponyms is better than the levels of acquisition for synonyms and antonyms. The data of this study ascertained that the developments of semantics, that is, the mastery of synonyms, antonyms and hyponyms among children, occur at different levels. Additionally, this study’s results recorded uneven children’s lexical or vocabulary developments. Hence, creating a linguistic atmosphere that is more fitting for preschool children is imperative because one can use it to explore the meanings of words and concepts among them in order further enhance their semantic acquisitions, in addition to using children’s songs and stories on YouTube.